The influence of price on seaweed farming growth: A case of East coast region of Zanzibar - Seif, Riziki Said. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as partial fulfillment of the requirements of the requirement for the award of the Master Degree of Business Administration –Corporate Management (MBA-CM) of Mzumbe University.